Future-Adapted Urban Structures Utopia, Vision, or Necessity? - Tietze, Wolf; Steinmann-Tietze, Maireluise (Promet - Traffic&Transportation, 2003)
Behavioural preferences of people are changing rapidly andmaking use of all sons of technical opponunities or progress.These changes mark a general and global process usually summarizedby the term 'urbanization' - rightly referring to urbansettlements. Towns and cities are parlicularly prominent manifestationsof cultural achievements of mankind. They are, atthe same time, the most imporlant means of housing, and aretools to create the values for the material base of life. Most citiesand towns do, however, cope no more with the speed of development,they lag behind and end up in structural chaos, theyfail to adapt to the future requirements. As analysis reveals, theforemost reason is inadequate location of functions resulting inunnecessary traffic. Urban settlements are inefficient, indeed,strangling themselves.To help solve this problem a model is presented here of afull-fledged city of average size. Implementation may be accomplishedpiecemeal. It is a realistic target, it is not utopia butnecessity.